Good medical practice in a time of chronic disease: time to retrace our steps? - Anand Bhopal (Edinburgh University Global Health Society, 2016)
In contemporary society, a wide range of non-communicable diseases, drug resistance and infectious ailments flourish. Yet the ability of doctors to tackle the multiple morbidities of patients is increasingly limited. This is part due to the ill-defined role of doctors in tackling population health issues such as the structural determinants of health which shape the social conditions in which disease thrives.